Cultural heritage and sustainable river management: incorporating local wisdom in Subayang River, Indonesia - Permatasari, Tika; Titisari, Prima Wahyu; Elfis, Elfis; Zen, Irina Safitri (UMT Press, 2024)
The Lubuk Larangan is a sustainable water resource management system that consists of a water system and a river. This study aims to explore the potential of cultural heritage and indigenous knowledge in relation to sustainable river management. The study was conducted in the villages of Gema and Tanjung Belit in the Riau Province, Indonesia. The data were collected through in-depth interviews, observation, and a review of the relevant literature. The collected data were analysed using descriptive qualitative analysis, which consisted of three stages: data reduction, data display, and conclusion drawing. The results indicate that the water system’s cultural practices have played a significant role in preserving the ecosystem, sustaining natural resources, and preserving water quality in the Subayang River. This study contributes to the growing body of literature. It provides a deeper understanding of the role of local wisdom and cultural heritage in achieving long-term ecological and social sustainability. Several factors, including geographical conditions, livelihood systems, customary law, and leadership patterns, support the ecological behaviour of a community in managing river resources.